THE CRIMINAL ACTS OF FRAUD REVIEWED IN A CRIMINAL LAW PERSPECTIVE: TINDAK PIDANA PENIPUAN DITINJAU DALAM PERSPEKTIF HUKUM PIDANA - Abdillah (UPMI Proceeding Series, 2023)
The crime of fraud is a crime that is closely related to property and consumer protection. The purpose of this study was to find out and analyze criminal acts of fraud from the perspective of criminal law. This type of research is normative with a statutory approach. The data used is secondary data consisting of primary and secondary legal materials. The crime of fraud is regulated in Chapter XXV Article 378 to Article 395 of the Criminal Code which is divided into 10 (ten) types, namely principal fraud, minor, buying and selling, scientific work, insurance, unfair competition, stellionaat. yard boundaries, giving an incorrect picture of securities and chartering. For this reason, it is recommended that members of the public not do it because there are criminal sanctions and it is very detrimental to other people.